ANALISIS DISPARITAS PENDAPATAN ANTAR KABUPATEN/KOTA DI JAWA TIMUR TAHUN 2008-2013 - Khusna, Lailatul (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2015)
This goals Â is finding out the level of income disparity among districts / cities in East Java, the determine the influence of the General Allocation Fund, Gross Domestic Product and educated workforce to income disparities among districts / cities in East Java and proving the hypothesis kuznets in EAST java.The analysis technique used is Entropy Theil, multiple linear regression by the method of Random Effects Model (REM) and trend analysis of the economic growth in East Java income disparity as proof Kuznets hypothesis. Research study shows that determinant coefficient (R2) is (0,974), means thet (97,4%), which is income disparities variabel influenced by independent variabel General Allocation Fund (DAU) (X1), Gross Regional Domestic Product (PDRB) (X2) and Educated Workforcelabour (TKTDD) (X3). The results showed the average income disparity districts / cities in East Java is high.Â